Folding Angle Measurement and Control Technology of Deformable UAV - Zheng Xiangming; Yin Chong; Wang Peng; Guo Shuzhen (Institute of Advanced Engineering and Science, 2013)
The deformable UAV has the advantage over the traditional fixed-wing aircraft in expanding the flight envelope. In this paper, a folding wing mechanism is designed to meet the accurate angle control requirement. Accordingly, an angle measurement method based on MEMS (micro-electromechanical systems) accelerometers is studied. The accurate folding angle in any condition can be derived from analysis of the folding wing’s acceleration in different positions, upon which the fuzzy control law of the wing’s folding angle is proposed. Finally, the validity and accuracy of the algorithm is verified with experiment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2345